Application and efficacy of pain combined with psychological intervention nursing in patients with craniocerebral trauma combined with ocular trauma after decompressive craniectomy - Li, Jing; Xu, Dongjing; Jia, Zhenling; Li, Jia; Shan, Yuchao (Journal of the Pakistan Medical Association, 2025)
Objective: To analyse the clinical effect of pain nursing combined with psychological intervention nursing on patients with traumatic brain injury and eye injury after decompressive craniectomy. Method: The retrospective study was conducted from January 1 to March 31, 2024, at the Baoding No. 1 Central Hospital, China, and comprised data from June 2019 to June 2023 of patients with ocular trauma who had undergone unilateral decompressive craniectomy. Control group A had received psychological intervention nursing, while intervention group B had additionally received pain nursing. The groups were compared for sleep quality, psychological resilience, pain level, self-care ability, mental state, and nursing satisfaction. Data was analysed using SPSS 21. Results: Of the 90 patients, 45(50%) were in group A; 31(68.9%) males and 14(31.1%) females with mean age 48.96±12.65 years (range: 25-76 years). Group B had 45(50%) patients; 34(75.6%) males and 11(24.4%) females with mean age 49.22±13.00 years (range: 23-75 years) (p>0.05). Across all parameters, both the groups showed significant improvement (p<0.05), but the degree of improvement was greater in group B compared to group A (p<0.05). The nursing satisfaction score of group B was significantly higher than that of group B (p<0.001). Conclusion: Pain combined with psychological intervention nursing could significantly improve the pain level, sleep quality and negative psychology of patients with traumatic brain injury and eye injury undergoing decompressive craniectomy, enhance psychological resilience, and improve patients’ self-care ability and nursing satisfaction. Key Words: Pain education, Psychological intervention, Craniocerebral trauma, Ocular trauma, Decompressive craniectomy, Clinical effect.